2015
DOI: 10.1016/j.aam.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-cores, posets, and lattice paths

Abstract: Hooks are prominent in representation theory (of symmetric groups) and they play a role in number theory (via cranks associated to Ramanujan's congruences). A partition of a positive integer n has a Young diagram representation. To each cell in the diagram there is an associated statistic called hook length, and if a number t is absent from the diagram then the partition is called a t-core. A partition is an (s, t)-core if it is both an s-and a t-core. Since the work of Anderson on (s, t)-cores, the topic has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 11 publications
1
63
0
Order By: Relevance
“…Amdeberhan [1] used this formula to obtain some identities for Catalan numbers. Besides, Lemma 3.3 leads to many interesting corollaries.…”
Section: Proof Lemma 32 Provides the Bijection Between (1) And (2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Amdeberhan [1] used this formula to obtain some identities for Catalan numbers. Besides, Lemma 3.3 leads to many interesting corollaries.…”
Section: Proof Lemma 32 Provides the Bijection Between (1) And (2)mentioning
confidence: 99%
“…Core partitions of numerous types of additional restrictions have long been studied, since they are closely related to the representation of symmetric group [15], the theory of cranks [13], Dyck-paths [1,3,28], and Euler's theorem [22]. To solve core problems, mathematicians provide many different tools, including t-abacus [3,15], Hasse diagram [27,28] and even ideas from quantum mechanics [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is a (6, 8)-core partition since none of its hook lengths is divisible by 6 or 8. Simultaneous core partitions have been widely studied in the past fifteen years (see [2,4,7,8,9,12,14,15,17,19,20,23]) since Anderson's work [3], who showed that the number of (t 1 , t 2 )-core partitions is equal to (t 1 + t 2 − 1)!/(t 1 ! t 2 !…”
Section: Introductionmentioning
confidence: 99%
“…. Other results in this area are due to Amdeberhan and Leven [5], Yang, Zhong, and Zhou [22], Aggarwal [1], and Wang [19].…”
mentioning
confidence: 98%